Au croisement des cultures, des discours et des langues. Cent ans d’études romanes a l’Université de Varsovie (1919–2019). Tome II: Linguistique et Didactique du FLE (University of Warsaw Press, 2025)
The book is part of celebrations of the 100th anniversary of the Institute of Romance Studies and its scientific and didactic activity in the field of French and Romance studies. The articles concern French literature, as well as the literature of Belgium, Switzerland and Quebec and cover the period from the 17th to the 21st century. The authors analyse major novels, short stories, essays, dramas as well as selected epistolography and reportage, they indicate the places where literature meets painting and photography meets cinema. The volume offers a wide selection of critical discourses such as: history, history of ideas, narratology, genology, intermediality, post-colonial studies, geocriticism, ecocriticism, which dominate francophone literary research.